Applicability of Endemic, Disaster and Resilience Strategies to Climate Impacts in the 21st Century: The Case of the Archaeological Territory of the City of Copán Ruins in Honduras - Vieira, Julia Colauto; Arriagada , Carlos Andrés Hernández; Madariaga , Javier; Arriagada, Giovana L. Hernández; Su Turhan, Ana Carolina (Technical and Scientific Journal Green Cities, 2024)
The city of Copán Ruinas, located in the department of Copán, Honduras, and located near the border with Guatemala, is home to one of the richest archaeological zones of the ancient Mayan empire. Due to its universal value, it was declared a World Heritage Site by UNESCO in 1980. However, in recent years, recurrent climate change in the area has put the Mayan legacy preserved there at risk. Floods, hurricanes and endemic crises in the region have increased, highlighting the urgency of protective measures. This research aims to discuss climate impacts and their consequences in an area of archaeological protection, with emphasis on floods, landslides and increased cases of respiratory diseases. Thus, using the method of implementing strategies for the creation of future scenarios focused on territorial restructuring, it is possible, based on analyses and diagnoses of the area, to propose actions that aim to contain the impacts in the region through public policies.